Digital Marketing Strategy and Its Impact on Consumer Loyalty - Widarianti, Ni Ketut Oni (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid advancement of digital technology has fundamentally transformed contemporary marketing practices and reshaped the patterns of interaction between companies and consumers. The increasing penetration of the internet, the widespread use of social media, and the dominance of mobile devices in Indonesia have created a dynamic and highly competitive digital ecosystem. These conditions require companies not only to adapt to technological changes but also to strategically optimize digital marketing as a primary approach to building and sustaining competitive advantage. In this context, digital marketing is no longer viewed merely as a promotional tool, but rather as a strategic mechanism for creating value, enhancing customer experience, and fostering long-term relationships with consumers. This study aims to systematically examine digital marketing strategies and their implications for customer loyalty through a comprehensive literature review. The research employs a qualitative descriptive approach using a library study method, involving an in-depth analysis of various relevant and up-to-date academic sources, including national and international journal articles, reference books, and scholarly publications related to digital marketing and customer loyalty. The collected data are analyzed by identifying recurring patterns, key concepts, and causal relationships derived from previous empirical and conceptual studies. The findings indicate that digital marketing strategies contribute significantly to the development of customer loyalty through several key dimensions, namely digital content quality, the intensity and quality of interactions, data-driven personalization, digital trust, and platform-based customer experience. In the digital context, customer loyalty is not solely reflected in repeat purchase behavior, but also in active engagement, willingness to provide positive recommendations, and tolerance toward price changes.